Pengaruh Pop Up Book Pakaian Adat Tradisonal Minangkabau terhadap Kemampuan Menyimak pada Anak Usia 5-6 Tahun di Taman Kanak- Kanak Aisyiyah 1 Bukittinggi - Arni, Arni; Ismet, Syahrul (ARZUSIN, 2023)
This study aims to analyze the influence of pop up books on traditional Minangkabau clothing on the listening skills of children aged 5-6 years at the Aisyiyah Bukittinggi kindergarten. The research method that will be used in this research is Quasi Experiment. The population in this study was Aisyiyah 1 Bukittinggi Kindergarten. The sampling technique in this study used cluster sampling. Based on pre-test and post-test data, the average gain score for the experimental class was 17.67. Meanwhile, the average gain score for the control class was 12.73. Thus there is a significant difference between the control class and the experimental class. So it can be concluded that Ha is accepted and Ho is rejected. The research results show that the use of the Pop Up Book media experimental method, Minangkabau Traditional Clothing, has an effect on the listening skills of young children.